MANAJEMEN PSIKOLOGI PELAYANAN DAN HOSPITALITY DALAM PENINGKATAN WISATAWAN MANCANEGARA - Sri Sunarti (Tulisan Ilmiah Pariwisata (TULIP), 2020)
The purpose of this study is to analyze the form of psychological management in service and hospitality to increase foreign tourists in love island tourism, Boalemo district, Gorontalo province. In this study, researchers used descriptive qualitative research methods. The results show that the existence of the hospitality industry has a positive impact on the growth of the number of foreign tourists and has an impact on increasing income for the people of Boalemo Regency. And quality services and according to guest needs can have an impact on guest satisfaction levels. The level of guest satisfaction with the quality of service provided is a comprehensive assessment of the superiority of a service related to facilities, services, and good employee responses, can give a good impression or experience for guests, so that it can create a sense of trust and loyalty.